Preclinical Evidence and Possible Mechanisms of Baicalein for Rats and Mice With Parkinson's Disease: A Systematic Review and Meta-Analysis - Wang, Yu; Wei, Na; Li, Xiaoliang (Frontiers in Aging Neuroscience, 2020)
Baicalein, a major bioactive flavone of Scutellaria baicalensis Georgi, has neuroprotective properties in several animal models of Parkinson’s disease (PD). Here, we conducted a systematic review and meta-analysis to assess the available preclinical evidence and possible mechanisms of baicalein for animal models of PD. Ultimately, twenty studies were identified by searching 7 databases from inception to December 2019. Review Manager 5.3 was applied for data analysis. Meta-analyses showed baicalein can significantly improve neurobehavioral function in animal models with PD, including spontaneous motor activity test (n = 5), pole test (n = 2), rotarod test (n = 9), apomorphine-induced rotations test (n = 4), grid test (n = 2), and tremor test (n = 2). Compared with controls, the results of the meta-analysis showed baicalein exerted a significant effect in increasing the frequency of spontaneous activity, prolongating the total time for climbing down the pole, decreasing the number of rotations, prolongating the descent latency, reducing the amplitude and the frequency in animal models with PD. The possible mechanisms of baicalein for PD are regulating neurotransmitters, adjusting enzyme activity, antioxidation, anti-inflammatory, inhibiting protein aggregation, restorating mitochondrial dysfunction, and anti-apoptosis. In conclusion, these findings preliminarily demonstrated that baicalein exerts potential neuroprotective effects through multiple signaling pathways in animal models of PD.